2022
DOI: 10.3389/fcimb.2021.804059
|View full text |Cite
|
Sign up to set email alerts
|

Use of Clinical Isolates to Establish Criteria for a Mouse Model of Latent Cryptococcus neoformans Infection

Abstract: The mechanisms of latency in the context of C. neoformans infection remain poorly understood. Two reasons for this gap in knowledge are: 1) the lack of standardized criteria for defining latent cryptococcosis in animal models and 2) limited genetic and immunological tools available for studying host parameters against C. neoformans in non-murine models of persistent infection. In this study, we defined criteria required for latency in C. neoformans infection models and used these criteria to develop a murine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…C. neoformans is known to cause a latent, subclinical infection in 99% of the human population, although some researchers suggest that it could be considered to be a member of the lung microbiome [ 34 ]. Cryptococcosis is thought be caused by the reactivation of latent infection in the context of immune deficiency [ 35 , 36 ] However, H99 is highly pathogenic in animal models of cryptococcosis, and even as few as five cells can cause lethal disease [ 37 ], precluding its use for latent infection models. Instead, another reference strain, 52D, was initially used to develop latent models of cryptococcosis [ 38 , 39 , 40 ].…”
Section: Advantages and Disadvantages Of Reference Isolatesmentioning
confidence: 99%
See 3 more Smart Citations
“…C. neoformans is known to cause a latent, subclinical infection in 99% of the human population, although some researchers suggest that it could be considered to be a member of the lung microbiome [ 34 ]. Cryptococcosis is thought be caused by the reactivation of latent infection in the context of immune deficiency [ 35 , 36 ] However, H99 is highly pathogenic in animal models of cryptococcosis, and even as few as five cells can cause lethal disease [ 37 ], precluding its use for latent infection models. Instead, another reference strain, 52D, was initially used to develop latent models of cryptococcosis [ 38 , 39 , 40 ].…”
Section: Advantages and Disadvantages Of Reference Isolatesmentioning
confidence: 99%
“…However, 52D is a C. deneoformans reference strain, and this species only causes 4% of infections in cryptococcal meningitis patients overall and only 1% in patients with HIV, as opposed to C. neoformans , which causes 95% and <99% of cryptococcosis cases, respectively [ 1 ]. To overcome this issue, we turned to clinical isolates to identify C. neoformans strains capable of establishing latent infections and used these strains to develop a latent murine model of cryptococcosis [ 35 ].…”
Section: Advantages and Disadvantages Of Reference Isolatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cryptococcus infection can be carried out in various ways, including intranasally, intratracheally, intracerebrally, intraperitoneally, and intravenously (Anderson & Sagha, 1988; Capilla et al., 2006; Coelho et al., 2019; Hamed et al., 2023; Kawakami et al., 1994; Lim et al., 1980; Mukaremera et al., 2019). Recent evidence indicated that disease progression from initial inhalation of Cryptococcus into the lungs to disseminated disease recapitulated human infection and disease outcomes (Coelho et al., 2019; Ding et al., 2021; Mukaremera et al., 2019; Normile et al., 2020). Compelling studies showed that humans and mice infected with the same C. neoformans strain exhibited similar outcomes for fungal burdens and mortality (Ding et al., 2021; Mukaremera et al., 2019; Normile et al., 2020).…”
Section: Introductionmentioning
confidence: 99%